2012
DOI: 10.1103/physrevlett.109.024504
|View full text |Cite
|
Sign up to set email alerts
|

From Sticky to Slippery Droplets: Dynamics of Contact Line Depinning on Superhydrophobic Surfaces

Abstract: This study explores how surface morphology affects the dynamics of contact line depinning of an evaporating sessile droplet on micropillared superhydrophobic surfaces. The result shows that neither a liquid-solid contact area nor an apparent contact line is a critical physical parameter to determine the depinning force. The configuration of a contact line on a superhydrophobic surface is multimodal, composed of both two phases (liquid and air) and three phases (liquid, solid, and air). The multimodal state is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
157
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(171 citation statements)
references
References 30 publications
(39 reference statements)
10
157
0
4
Order By: Relevance
“…We note that, although λ s in Eq. 10 may appear similar to the semi-empirical parameters commonly proposed in the literature 3,11,31 , λ s is fully analytical. Instead, λ s depends not only on the structure geometries but also on the receding conditions (e.g., direction), as illustrated in Figure S4.…”
Section: Model Generalization For 3-d Recedingsupporting
confidence: 52%
See 1 more Smart Citation
“…We note that, although λ s in Eq. 10 may appear similar to the semi-empirical parameters commonly proposed in the literature 3,11,31 , λ s is fully analytical. Instead, λ s depends not only on the structure geometries but also on the receding conditions (e.g., direction), as illustrated in Figure S4.…”
Section: Model Generalization For 3-d Recedingsupporting
confidence: 52%
“…Unlike the well-organized microstructures used for the scientific studies 1,7,12,13,19,31 , the roughness found in nature and industrial applications are normally of random pattern and twotier in micro-and nanoscale. Noting the summation nature of Eq.…”
Section: Figurementioning
confidence: 99%
“…In this state, the water droplet would be in contact with the surface at all points and the liquid/solid contact area would be further increased. [66][67][68] Thus, as shown in Figure 7, if the pH is increased from 7 to 12, the adhesive force between the surface and the water droplet would increase and it would be reasonable to conclude that high adhesion between the surface and the basic droplet would arise not only because of the hydrophilic properties of the deprotonated carboxylic acid groups, but also owing to the transition of the wetting states. After being rinsed with pure water and dried with N 2 , the deprotonated carboxylic acid group would return to being protonated, and thus, the surface would return to its initial low-adhesive state for acidic or neutral water droplets.…”
Section: Resultsmentioning
confidence: 95%
“…yağmur damlalarıyla), buzlanmanın önlenmesi, paslanmanın önlenmesi, sürüklenme direncinin düşürülmesi, yoğuşma/kaynama ve mikro cihazlar gibi alanlarda uygulama potansiyeline sahiptirler [5].…”
Section: Hidrofobik Yüzeylerin Uygulama Alanlarıunclassified
“…Bu sebeple temas açısı histerezisi ve özellikle gerileyen temas açısı büyük değerlerde olmaktadır. Yapışkan süperhidrofobik yüzeyler sprey ve boyama uygulamalarında, mikro cihazlarda, mürekkep püskürtmeli baskı ve sıvı transfer uygulamalarında kullanım potansiyeline sahiptirler [5].…”
Section: Hidrofobik Yüzeylerin Uygulama Alanlarıunclassified